‘Batu Reput’ used as raw material in fertilizer production - Mohd Nazry, Salleh; Farizul Hafiz, Kasim; Khairul Nizar, Ismail; Che Mohd Ruzaidi, Ghazali; Kamarudin, Hussin; Saiful Azhar, Saad; Suhardy, Daud (Malaysian Institute for Nuclear Technology Research (MINT), Xapp Malaysia-MNS & Universiti Kebangsaan Malaysia (UKM), 2008)
Organized by Malaysian Institute for Nuclear Technology Research (MINT), Xapp Malaysia-MNS & Universiti Kebangsaan Malaysia (UKM), 29th - 30th November 2006 at Palm Garden Hotel IOI Resort, Putrajaya, Malaysia.